The Effect of Audit Reports and KAP Measurements on The Relevance of The Value Accounting Information - Windi Nawati; Tubagus Ismail; Munawar Muclish (Journal of Applied Business, Taxation and Economics Research, 2022)
The purpose of this study was to determine The Effect of Audit Reports and KAP Measurements on The Relevance of The Value Accounting Information in banking companies listed on the Indonesia stock exchange 2016-2020. The sample used in this study is 10 pharmacy companies. The data used is secondary data. The data analysis technique used is quantitative. Structural Equation Modeling is used as an analysis with the help of Smart SPSS software version 23. Based on the results of the study, it can be concluded that the first audit report has a significant positive effect on book value per share. Second, the audit report has a significant positive effect on the value of earnings per share. Third, KAP size has a significant positive effect on book value per share. Fourth, the size of KAP has a significant positive effect on the value of earnings per share.